1993
DOI: 10.1111/j.1432-1033.1993.tb17918.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, sequence analysis and expression of the gene for catalase‐peroxidase (cpeA) from the photosynthetic bacterium Rhodobacter capsulatus B10

Abstract: The gene encoding catalase-peroxidase was cloned from chromosomal DNA of Rhodobacter capsulatus B10. The nucleotide sequence of a 3.7-kb Sad-Hind111 fragment, containing the catalase-peroxidase gene (cpeA) and its flanking regions were determined. A 1728-bp open reading frame, coding for 576 amino acid residues (molecular mass 61 516 Da) of the enzyme, was observed. A Shine-Dalgarno sequence was found 5 bp upstream from the translational start site. The deduced amino acid sequence coincides with that of the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Among the others, L. pneumophila CuZnSOD is also periplasmic (52), but the catalase-peroxidases of C. crescentus (51) and R. capsulatus (18,19,27,29) have not been subjected to localization studies and are not predicted to contain a signal peptide (PSORT Prediction, http://psort.nibb.ac.jp/form.html; Signal P V1.1, http://www.cbs.dtu.dk/services/signalP/). Our studies raise the question of whether a periplasmic location is a sine qua non for the stationary-phase function.…”
Section: Discussionmentioning
confidence: 99%
“…Among the others, L. pneumophila CuZnSOD is also periplasmic (52), but the catalase-peroxidases of C. crescentus (51) and R. capsulatus (18,19,27,29) have not been subjected to localization studies and are not predicted to contain a signal peptide (PSORT Prediction, http://psort.nibb.ac.jp/form.html; Signal P V1.1, http://www.cbs.dtu.dk/services/signalP/). Our studies raise the question of whether a periplasmic location is a sine qua non for the stationary-phase function.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the steric hindrance that does not provide access to the heme prosthetic group of the enzyme (62). Secondly, comparison of the conserved motifs in the KatB amino acid sequence revealed that the heme-binding ligands and active-site residues are highly conserved with the true catalases, whereas the conserved active site and domains of peroxidases that are present in bacterial catalase-peroxidases (19,73) were not identified in the B. fragilis catalase. The restricted peroxidatic activity associated with B. fragilis KatB is probably due to the nonspecific catalysis that occurs in typical catalases toward certain types of organic electron donor compounds (62).…”
Section: Fragilismentioning
confidence: 99%
“…Little is known about the conditions prevailing in the bacterial cells following the establishment of respiration, but oxygen-centered derivatives such as superoxide and peroxides are expected to be produced by reduced intermediates of the electron transport chain (36). In line with this assumption, a number of protective antioxidant proteins are known to be present in Rhodobacter species, including two peroxidases (12) and an oxygen-responsive thioredoxin which is essential for both aerobic and anaerobic growth (28). We have recently identified a single SOD (SOD Rc ) in R. capsulatus cells cultured under various growth regimes (8).…”
mentioning
confidence: 97%